Research on the Application of CAD Auxiliary Intelligent Technology in Sports. (17th January 2022) - Wang, Wenhong
Abstract : This paper mainly combines CAD auxiliary intelligent technology and image processing technology, by combining the experience and creativity of sports coaches and sports researchers, and using modern technology, it can design and efficiently study sports quickly, conveniently, and efficiently and uses advanced high-tech technology to replace the traditional relatively backward artificial design method of sports. In the field of sports, in-depth research and scientific research and feasibility analysis can be conducted, so as to realize the design of CAD auxiliary intelligent technology system for sports competitive movements. Finally, the experimental results show the CAD auxiliary intelligence technology in sports to verify the feasibility and have practical value.